Students’ Mathematical Literacy with Realistic Mathematics Education (RME) Approach: Systematic Literature Review - Farah Ayyun Taqiya; Dadang Juandi (Department of Mathematics Education University of Muhammadiyah Malang, 2023)
This study intends to examine how the Realistic Mathematic Education (RME) learning approach affects students' mathematical literacy skills at the primary, junior, and senior high school education levels. The Systematic Literature Review (SLR) method is employed in this investigation. 11 RME learning study findings on mathematical literacy from indexed journals published between 2016 and 2022 make up the dialysis sample. What factors, such as education level, research year, number of student samples used, or location study, affect students' mathematical literacy skills is the topic of the study. The analysis findings indicate that learning using the RME approach to mathematical literacy is increasing annually. This research is typically conducted on the island of Java with a small sample size of students, specifically less than 30 students, and junior high school students are the target population. Based on the review's findings, it can be concluded that using the RME approach to instruction can enhance or have an impact on students' mathematical literacy abilities.